The Essence and Role of Educators in Islam: Qualifications, Revitalization, and Transformation in the Contemporary Era - Bahrianti B; Afifuddin Harisah; Syarifuddin Ondeng (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This article comprehensively examines the nature and role of educators in Islam, encompassing three main pillars: parents, teachers, and community figures. The study focuses on three main issues: (1) the concept and typology of educators in Islam, (2) educator qualifications and strategic roles, and (3) the moral, spiritual, and social responsibilities of educators in a contemporary context. Using a library research approach referring to the Qur’an, hadith, classical Islamic scholars’ thoughts, and modern educational theories, this article finds that Islamic educators bear a triple role as mu’allim (teacher), murabbi (character builder), and mursyid (spiritual guide). The challenges of globalization and the Industrial Revolution 4.0 necessitate the revitalization of educator competencies without abandoning fundamental Islamic values. The transformation of educational paradigms from teacher-centered to student-centered is an inevitability of this era.